Are the Democrats Really So Stupid? (Tufts Archival Research Center, 2007)
New York Times op-ed by Robert McIntyre criticizing the Democrats' approach to the Federal budget defecit. Accuses Democrats of encouraging higher taxes for the working class and cuts in Social Security benefits while refusing to raise income taxes on the wealthy. Identifies tax breaks for wealthy Americans as the root cause of the Federal defecit. Questions whether anyone stands for the working class.